Benefits of the Retrocaruncular Approach to the Medial Orbit: A Clinical And Anatomic Study. Issue 3 (March 2016) - Kempton, Steve J.; Cho, David C.; Thimmappa, Brinda; Martin, Mark C.
Abstract : Background: Current trends in the management of medial orbital wall fractures are toward the development of transconjunctival incisions and the use of endoscopic-assisted methods. Different authors have suggested variations of the medial transconjunctival approach. Methods: (1) In 30 fresh cadaver orbits, the classic transcaruncular approach was compared with the precaruncular and retrocaruncular approach under magnified dissection. (2) A retrospective analysis was conducted on a series of 20 consecutive patients that underwent primary repair of medial orbital wall fractures using a retrocaruncular approach without endoscopic assistance. Postoperative computed tomography scans were obtained for all patients and were evaluated by 3 experienced clinicians. Results: (1) Anatomic dissections showed that all 3 approaches provided excellent exposure of the entire medial orbital wall. The transcaruncular and precaruncular approaches, however, (a) both resulted in exposure of the upper and lower tarsi when incisions greater than 10 mm were used; (b) both required a transition from the preseptal plane to the postseptal plane when combined with inferior fornix incisions. (2) A clinical study of 20 patients showed all reconstructions were possible without endoscopic assistance, resulting in no postoperative complications. Postoperative computed tomography scans showed anatomic orbital reconstruction in all patients judged as excellent by the clinicians. Conclusions: Medial orbital wall fractures can be successfully repaired using transconjunctival incisions without using endoscopes. The retrocaruncular approach surpasses the transcaruncular and precaruncular methods due to its decreased risk of postoperative lid complications and its ability to be directly carried to the inferior conjunctival fornix.